EFFECT OF ALLELOPATHY OF PARTHENIUM HYSTEROPHORUS L. AND LANTANA CAMARA L. IN DIFFERENT CONCENTRATION WITH DISTILL WATER ON SEED GERMINATION OF PHASEOLUS RADIATUS L. - Ashish Singh Tomar (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Parthenium hysterophorus L. and Lantana camara L. are collected there extract of leaf and shoot are mixed and prepared with distilled water in different concentration 5%, 10%, 15%, 20% distilled water is taken as controlled now these extract is used on the crop Phaseolus radiatus L. which is a leguminous plant the material chosen for the study includes Parthenium hysterophorus L and Lantana camara L. the leaf and shoot of these plant is collected dried and with the help of mixture grinder extract was made after that the extract is mixed and soaked for 24 hours in Distilled water and then following concentration of extract in distilled water is prepared the concentration are as follows 5:95%, 10:90%, 15:85%, 20:80% distilled water is used as control respectively. Now the different concentration of extract is used on the seed of Phaseolus radiatus L. and seed germination is recorded. The data are taken and collected through static. The highest germination we see in control Distilled Water is 100% and at 5:95% and 10:90% the 90% seed germination is seen in 15:85% we got 70% germination and in 20:80% the seed germination is 60% so the allelochemicals released by Parthenium hysterophorus L. and Lantana camara L. aqueous extract has the inhibitory effect on seed germination So we are absorbing that the Allelochemicals produced by Parthenium hysterophorus L. and Lantana camara L. aqueous extract is giving very adverse effect and inhibits seed germination of Phaseolus radiatus L.